FACTORS THAT STIMULATE THE ECOSYSTEM ROMANIAN ENTREPRENEURIAL - ENEA CONSTANŢA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2017)
Entrepreneurship has begun to grapple with the global economic and financial crisis, and entrepreneurs have become "heroes" capable of delivering impetus to fragile economies. Small and innovative companies account for 99% of all Europe's active companies and offer 66% of available jobs. In the context of a worrying unemployment rate that persists in many countries of the world, entrepreneurship has become a viable solution to economic problems. Entrepreneurship can not be defined precisely, and the multidimensionality and homogeneity of the concept makes it very difficult to generalize the conclusions of studies for regions other than those for which they were originally developed. The objective of the present study is to carry out a comprehensive analysis of the Romanian entrepreneurial ecosystem and the factors that have the power to stimulate it, thus allowing the design of efficient policies for the development of Romanian entrepreneurship.